Integration of education and entertainment on Chinese television as a mechanism to preserve traditional values - Zheng, Li (Journal of the Belarusian State University. Journalism, 2023)
The issues of integration of the sphere of education and the entertainment industry in the context of preserving traditional Chinese values are considered. The differences between the educational potential of entertainment television programs and the possibilities of traditional Chinese education are analysed. The reality shows «First lesson» and «Chinese character dictation» are explored as examples of the effective integration of education and entertainment on Chinese television.